(untitled) (Acta Entomologica Serbica, 2021)
The diversity of species of Cotesia Cameron, 1891 for the territory of Serbia is given as a faunistic survey. The paper presents the results of research in the period from 1902 to 2021. Literature, databases and new, unpublished records were combined for a comprehensive list of species, with notes on localities, dates, number and sexes of individuals. In total, 35 species are presented, of which 11 were registered in Serbia for the first time. The species most often collected were Cotesia ofella and C. tibialis.